2017
DOI: 10.13005/ojc/330549
|View full text |Cite
|
Sign up to set email alerts
|

Supercritical Fluid Extraction as a Technique to Obtain Essential Oil from Rosmarinus officinalis L.

Abstract: The aim of this study was the comparison of essential oil of one herb from lamiaceae family namely Rosemary, via supercritical fluid extraction (SFE) and hydrodistillation (HD). The essential oils were analyzed by gas chromatography-quadrupole mass spectrometry (GC-MS). The compounds identified in higher relative abundance were,α-pinene (HD: 30.42%, SFE: 0.47%), 1,8-cineole (HD: 15.46%, SFE: 25.05%),Verbenone (HD: 13.09%, SFE: 5.17%), Camphor (HD: 8.97%, SFE:15.69%), Borneol (HD: 7.16%, SFE: 9.15%) and β∋-Cary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…However, the supercritical fluid extraction (SFE) resulted in higher yields of EO when compared with steam and HD (Conde‐Hernandez et al, ). Khalili, Mazloomifar, Larijani, Tehrani, and Pazar () also found that SFE is advantageous over HD by shorter extraction times, less energy consumption, and no need of polar cosolvent. The main components of R .…”
Section: Phytochemical Composition Of Rosmarinus Plantsmentioning
confidence: 96%
See 1 more Smart Citation
“…However, the supercritical fluid extraction (SFE) resulted in higher yields of EO when compared with steam and HD (Conde‐Hernandez et al, ). Khalili, Mazloomifar, Larijani, Tehrani, and Pazar () also found that SFE is advantageous over HD by shorter extraction times, less energy consumption, and no need of polar cosolvent. The main components of R .…”
Section: Phytochemical Composition Of Rosmarinus Plantsmentioning
confidence: 96%
“…However, the supercritical fluid extraction (SFE) resulted in higher yields of EO when compared with steam and HD (Conde-Hernandez et al, 2017). Khalili, Mazloomifar, Larijani, Tehrani, and Pazar (2017) also found that SFE is advantageous over HD by shorter extraction times, less energy consumption, and no need of polar cosolvent. The main components of R. officinalis EO were α-pinene (HD: 30.4% and SFE: 0.5%), 1,8-cineole (HD: 15.5% and SFE: 25.1%), verbenone (HD: 13.1% and SFE: 5.2%), camphor (HD: 9.0% and SFE:15.7%), borneol (HD: 7.2% and SFE: 9.2%), and β-caryophyllene (SFE: 6.8%).…”
Section: Rosemary Extracts: Insights On Eos Compositionmentioning
confidence: 99%
“…The total analysis time was 65.33 min. The carrier gas was He at a flow rate of 0.7 mL/min, injection volume of 2 µL, split ratio of 1:10, and injector temperature of 280 • C [25]. The Kovats retention index (RI) values were determined based on a homologous series of n-alkanes (C 8 -C 25 ).…”
Section: Gas Chromatography-mass Spectroscopy (Gc-ms) Analysismentioning
confidence: 99%